2007
DOI: 10.1038/nature05837
|View full text |Cite
|
Sign up to set email alerts
|

PHA-4/Foxa mediates diet-restriction-induced longevity of C. elegans

Abstract: Reduced food intake as a result of dietary restriction increases the lifespan of a wide variety of metazoans and delays the onset of multiple age-related pathologies. Dietary restriction elicits a genetically programmed response to nutrient availability that cannot be explained by a simple reduction in metabolism or slower growth of the organism. In the nematode worm Caenorhabditis elegans, the transcription factor PHA-4 has an essential role in the embryonic development of the foregut and is orthologous to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
547
5
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 513 publications
(590 citation statements)
references
References 48 publications
28
547
5
10
Order By: Relevance
“…Contrary to some of the previous studies performed in other species (Bartke et al 2001;Houthoofd et al 2003;Panowski et al 2007), our data clearly find that the insulin/IGF pathway and DR have significant interactions and may ultimately use the same pathways to extend lifespan. This has also been demonstrated in flies (Clancy et al 2002).…”
Section: Gompertz Analysiscontrasting
confidence: 99%
“…Contrary to some of the previous studies performed in other species (Bartke et al 2001;Houthoofd et al 2003;Panowski et al 2007), our data clearly find that the insulin/IGF pathway and DR have significant interactions and may ultimately use the same pathways to extend lifespan. This has also been demonstrated in flies (Clancy et al 2002).…”
Section: Gompertz Analysiscontrasting
confidence: 99%
“…If so, genetic determinants for this adaptation may exist similar to what was demonstrated recently for the existence of the two genes PHA-4 and SKN-1, both encoding for transcription factors, that mediate the effects of CR in the poikilotherms C. elegans [39,40]. PHA-4 is very similar to mammalian FOXA proteins that, in adult life, regulate glucose metabolism; SNK-1 is similar to the mammalian NRF2 and helps protect against oxidative stress.…”
Section: Temperature and Energy Homeostasissupporting
confidence: 57%
“…The restriction of food intake is one of the most powerful and robust ways to extend lifespan in a wide variety of organisms. Although this observation was first made by McCay in 1935 (McCay, Crowell, & Maynard, 1935), molecular mechanisms of nutritional‐mediated lifespan extension only started to be unraveled in 2007 (Bishop & Guarente, 2007; Panowski, Wolff, Aguilaniu, Durieux, & Dillin, 2007). We analyzed the lifespan of worms that were fed ad libitum or subjected to two different regimens of dietary restriction.…”
Section: Resultsmentioning
confidence: 99%
“…We first tested the impact of the forkhead transcription factor PHA‐4/FOXA known to be required for the dietary restriction response (Panowski et al, 2007). We found that pha‐4 mRNA levels were induced upon dietary restriction in controls, but not in C8‐SA‐treated worms (Supporting information Figure S3a).…”
Section: Resultsmentioning
confidence: 99%